The Effect of Chronic Alcohol on Cognitive Decline: Do Variations in Methodology Impact Study Outcome? An Overview of Research From the Past 5 Years - Charlton, Annai J.; Perry, Christina J. (Frontiers in Neuroscience, 2022)
Excessive alcohol use is often associated with accelerated cognitive decline, and extensive research using animal models of human alcohol consumption has been conducted into potential mechanisms for this relationship. Within this literature there is considerable variability in the types of models used. For example, alcohol administration style (voluntary/forced), length and schedule of exposure and abstinence period are often substantially different between studies. In this review, we evaluate recent research into alcohol-induced cognitive decline according to methodology of alcohol access, as well as cognitive behavioral task employed. Our aim was to query whether the nature and severity of deficits observed may be impacted by the schedule and type of alcohol administration. We furthermore examined whether there is any apparent relationship between the amount of alcohol consumed and the severity of the deficit, as well as the potential impact of abstinence length, and other factors such as age of administration, and sex of subject. Over the past five years, researchers have overwhelmingly used non-voluntary methods of intake, however deficits are still found where intake is voluntary. Magnitude of intake and type of task seem most closely related to the likelihood of producing a deficit, however even this did not follow a consistent pattern. We highlight the importance of using systematic and clear reporting styles to facilitate consistency across the literature in this regard. We hope that this analysis will provide important insights into how experimental protocols might influence findings, and how different patterns of consumption are more or less likely to produce an addiction-vulnerable cognitive phenotype in animal models.